2021
DOI: 10.3389/fmars.2021.635890
|View full text |Cite
|
Sign up to set email alerts
|

Using Evidence From Voluntary Fisheries Data Collection Programmes to Support Marine Spatial Planning and Resolve Multiple-Use Conflicts

Abstract: Natural disasters have altered the landscape of Montserrat’s marine environment significantly over the past 30 years, forcing rapid adaptation of marine species and the human population that relies upon them. Volcanic activity has led to an abundance of volcanic sediment, which has seen rise to the expansion of the island’s sand mining and aggregate industry. Similarly, a series of volcanic eruptions has resulted in smothered fishing grounds and maritime exclusion zones, increasing the pressure on the remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…AIS data were less‐often used to depict fishing patterns, featuring in only 3% of articles (Figure 2b). Other vessel tracking technologies included the use of small Global Position System (GPS) devices attached to the boat (Dosell et al, 2021; Metcalfe et al, 2017; Zaykoski, 2016) or on‐board observers recording GPS locations at fixed time intervals (Mendo et al, 2019).…”
Section: Types Of Fisheries Sources Of Data and Metrics Usedmentioning
confidence: 99%
See 4 more Smart Citations
“…AIS data were less‐often used to depict fishing patterns, featuring in only 3% of articles (Figure 2b). Other vessel tracking technologies included the use of small Global Position System (GPS) devices attached to the boat (Dosell et al, 2021; Metcalfe et al, 2017; Zaykoski, 2016) or on‐board observers recording GPS locations at fixed time intervals (Mendo et al, 2019).…”
Section: Types Of Fisheries Sources Of Data and Metrics Usedmentioning
confidence: 99%
“…Most planning was done as a research exercise and only three articles explicitly indicated that their spatial plan was actually implemented (Dosell et al, 2021; Flower et al, 2020; Johnson et al, 2020). Interestingly, only one of these three real‐world cases used a quantitative method ( prioritizr ) to develop a spatial plan, albeit heavily edited by local stakeholders (Flower et al, 2020).…”
Section: Use Of Fisheries Data In Spatial Planningmentioning
confidence: 99%
See 3 more Smart Citations